(Anti-)Emancipatory answers from the Right - Bruns, Julian; Strobl, Natascha (Momentum Quarterly, 2015)
This article wants to show a recent development of a new spectrum within the extreme right. The New Right finds its references with the ‘Conservative Revolution’ and distances itself from Nationalsocialism. In the last 5-10 years a new generation of younger activists took over. In this article we show with the examples of CasaPound, the Identitarians, Frei.Wild, the Montagsmahnwachen and the Autonomen Nationalisten (who operate within a neonazistic spectra) how strategies and goals have been altered in the last decade. Leftist protestforms were incorporated and reframed. Right wing extremists contested meanings of terms like democracy and made them usable for right wing ideology. Their goal is hegemony and acceptance within bourgeois classes. The New Right, whose members belong to the privileged class within capitalist societies, disguise themselves as the true victims of a recent crisis. From that position they give alleged emancipatory answers. Behind these new strategies the same old right wing ideology can be found.